2021
DOI: 10.3389/fimmu.2021.754710
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Evaluation of Rhesus Macaque Fc Gamma Receptors Reveals Similar IgG Fc Glycoform Preferences to Human Receptors

Abstract: Rhesus macaques are a common non-human primate model used in the evaluation of human monoclonal antibodies, molecules whose effector functions depend on a conserved N-linked glycan in the Fc region. This carbohydrate is a target of glycoengineering efforts aimed at altering antibody effector function by modulating the affinity of Fcγ receptors. For example, a reduction in the overall core fucose content is one such strategy that can increase antibody-mediated cellular cytotoxicity by increasing Fc-FcγRIIIa aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Stabilizing the Fc glycan might be a factor that contributes to the higher affinity for the Man5 produced receptor to the macaque IgG2, IgG3, and IgG4 as compared to IgG1 and to the Val 158 variant. In summary, as has been the case for afucosylated glycans on the Fc for macaque IgGs ( 64 ), changes to the glycan composition on the macaque FcγRIII receptor can lead to changes in affinity to IgG. It remains to be seen if this change in affinity will translate to a change in function, particularly with regard to NK cells and their potentially altered FcγRIII glycan composition as has been the case for humans ( 65 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Stabilizing the Fc glycan might be a factor that contributes to the higher affinity for the Man5 produced receptor to the macaque IgG2, IgG3, and IgG4 as compared to IgG1 and to the Val 158 variant. In summary, as has been the case for afucosylated glycans on the Fc for macaque IgGs ( 64 ), changes to the glycan composition on the macaque FcγRIII receptor can lead to changes in affinity to IgG. It remains to be seen if this change in affinity will translate to a change in function, particularly with regard to NK cells and their potentially altered FcγRIII glycan composition as has been the case for humans ( 65 ).…”
Section: Discussionmentioning
confidence: 94%
“…Despite the close evolutionary proximity between humans and Rhesus macaques, Macacca mulata (Mm), there are many important differences in immune system genes and function between the two species that can confound the interpretation of results when macaques are used as an animal model. Some have been well documented, such as the gene duplication event that gave rise to FcγRIIIa and FcγRIIIb in humans ( 12 ) or the extended hinge region only present in human IgG3 ( 9 , 63 ), but others such as the effect of IgG glycoform on FcγRIII affinity in macaques have only more recently been examined ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the importance of sialic acid on N-glycans of the IgG Fc region is unclear. Some studies have suggested that sialylation of Fc N-glycan is necessary for the IgG anti-inflammatory properties 65 , 66 while more recent work showed that sialic acid does not affect recognition by Fc γ receptors (FcγRs) III 36 , 67 , 68 . Thus, despite major differences in IgG N-glycans, including the type of sialic acid, rhesus macaques might have Antibody-Dependent Cellular Toxicity mechanisms that are highly similar to humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, extrapolation of preclinical findings from macaques to humans can be compromised when subtle differences in biology exist. For example, interspecies differences between immunoglobulins and their Fc receptors raise questions about the suitability of macaques for development of human antibody therapies and vaccines, and the extent to which data from animal trials can be translated clinically 33 , 35 , 36 . Nonetheless, as of today, studies of rhesus macaque glycoconjugates have been limited to IgG N-glycans 28 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless one should bear in mind that mice do not have the equivalent of FcɣRIIIB, which therefore makes this species not completely adequate to test the role of PMN in antibody efficacy in vivo , unless fully humanized models are used ( 119 ). Despite these caveats, it is worth noting that afucosylated or low fucose anti-cancer mAbs have consistently been shown to control tumor growth more efficiently than their fully fucosylated parent molecules in mice ( 69 , 84 , 92 , 122 ), as well as macaque, the latter having a more similar pattern of FcɣRs to humans ( 123 ). These results have led to an increased attention to the N-glycan profile of therapeutic mAbs ( 124 ), as well as the development of new afucosylated therapeutic antibodies in a variety of clinical contexts.…”
Section: Evidence That Afucosylation Enhances the Efficacy Of Therape...mentioning
confidence: 99%